Arms and the People Popular Movements and the Military from the Paris Commune to the Arab Spring - Gonzalez, Mike; Barekat, Houman (Pluto Press, 2012)
This collection examines the relationship between mass movements and the military. Some argue that it is impossible to achieve and protect a revolution without the support of the army, but how can the support of the army be won? Arms and the People explores the impact of social extremes on the solidarity within the state's military, and on the changing loyalties of these soldiers. The authors examine a series of historical moments in which a crisis in the military has reflected deep instability in the wider world, including Russia in 1917, Egypt during the Arab Spring, the Paris Commune, as well as long-standing instability in Venezuela and Indonesia, amongst many others. Including a range of international authors who have either studied or been directly involved in such social upheavals, Arms and the People is a pioneering contribution to the study of revolutionary change.